2020
DOI: 10.1039/d0bm00443j
|View full text |Cite
|
Sign up to set email alerts
|

Tailorable hierarchical structures of biomimetic hydroxyapatite micro/nano particles promoting endocytosis and osteogenic differentiation of stem cells

Abstract: Hydroxyapatite (HA) micro/nano particles show great promise as artificial bone and dental substitutes, or drug carrier systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…Stimulation of HMSCs by HA raises the activity of the CREB transcription factor, which regulates several osteoblast marker genes. HA nanoparticles can enter the cytoplasm through the endosome and decompose into its ingredients, calcium, and phosphate [47]. Xu et al [47] revealed that increasing the intracellular concentration of calcium ions stimulates several signaling pathways, including calcium, cAMP, Ras, Rap1, and MAPK.…”
Section: Effect Of Hydroxyapatite On Cellular Behaviormentioning
confidence: 99%
“…Stimulation of HMSCs by HA raises the activity of the CREB transcription factor, which regulates several osteoblast marker genes. HA nanoparticles can enter the cytoplasm through the endosome and decompose into its ingredients, calcium, and phosphate [47]. Xu et al [47] revealed that increasing the intracellular concentration of calcium ions stimulates several signaling pathways, including calcium, cAMP, Ras, Rap1, and MAPK.…”
Section: Effect Of Hydroxyapatite On Cellular Behaviormentioning
confidence: 99%
“…Previous papers have typically used nanosize HA particles to fabricate scaffolds for bone tissue engineering. [ 35–39 ] Furthermore, these prior studies mainly focused on scaffold fabrication and in vitro cell response. [ 40–41 ] In addition, researchers have utilized HA in low concentrations in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the previous studies have used complex processing techniques to synthesize nanoscale HA particles such as nanoflakes and nanorods to evaluate osteogenic differentiation. [ 37–39 ] In our study, commercially available nonprocessed HA microparticles were used at different concentrations within a gelatin‐based hydrogel (GelMA) matrix to increase the mechanical stability of the resulting scaffolds and promote osteogenic differentiation of the preosteoblasts. [ 32–35 ] Our approach is a unique way to achieve highly tunable osteoinductive scaffolds and enables to control the osteogenic differentiation of predifferentiated stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Bone destruction is associated with severely imbalanced bone remodeling, secondary to increased osteoclastogenesis and significant osteoblast suppression, which leads to serious bone loss and cause the stability of titanium plants to be endangered even with a hydroxyapatite coating. [30][31][32] Therefore, it is of great significance to increase the bone induction ability of joint prosthesis by eliminating possible interfering factors for the treatment of orthopedic diseases.…”
Section: Discussionmentioning
confidence: 99%